An Axiological Analysis of School Radio as a Tool for Internalizing Courage and Language Ethics in Indonesian Language Learning - Rischa Anggraeni Basuki; Anas Ahmadi (Raja Zulkarnain Education Foundation, 2026)
The purpose of this study is to investigate the axiological aspect of school radio as a tool for internalizing courage and language ethics in Indonesian language learning. This study employs interpretative axiological analysis, a case study design, and a descriptive qualitative methodology. Students from SMP Negeri 18 Surabaya who participate in the school radio broadcaster served as the study's subjects. Participatory observation of broadcast activities, teacher and student interviews, and an examination of the school radio program's documentation were all used to gather data for this study. The results of teacher and student interviews, observations, and various documents pertaining to school radio broadcast activities were compared in order to preserve the validity of the data using triangulation techniques and sources. Data reduction, systematic data presentation, and extracting conclusions from field data were the steps in the data analysis process used in this study. The goal of all data gathering and analysis methods was to get a comprehensive understanding of the philosophy of science, particularly the axiological component of learning Indonesian language and literature literacy. The study's findings show that school radio has axiological significance as a useful medium for teaching language and character. Students' direct participation in the design and execution of broadcasts demonstrates their internalization of the value of courage, which boosts their self-assurance and capacity for candid communication. In the meantime, the implementation of language rules during broadcasts, accountability for broadcast content, teacher direction, and the presence of communicative and ongoing reflection can all contribute to the internalization of ethics in language. This study has demonstrated that, in the context of teaching Indonesian, school radio serves as both a technological means of disseminating information and a learning laboratory that can help students develop their character.